Clinical Features and Laboratory Findings, Among Children with Covid-19 in Pak Emirates Military Hospital, Rawalpindi - Bashir, Junaid; Ahmed, Zeeshan; Ghafoor, Muzzamal; Hussain, Murtaza; Aziz, Atif; Babar, Muhammad Waleed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To study the clinical features among children admitted to Pak emirates Military Hospital with laboratory confirmed COVID-19 infection in Pakistan. Study Design: Cross sectional study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Aug 2020 to Mar 2021. Methodology: All patients between 2 years to 12 years of age, either sex, who had presented with a confirmed diagnosis of COVID-19 in Pak Emirates Military Hospital Rawalpindi, during the study period, were included in this study. Results: There were a total of 64 COVID-19 confirmed cases in our study. The mean age was 7.9±2.45 years. There were 37(57.8%) male patients and 27(42.2%) female patients. Among the symptomatic patients: fifty-four (84.4%) patients had fever, 29(45.3%) had cough, 17(26.65%) had sputum production, 18(28.12%) had dyspnea, 7(10.9%) had sore throat, 16(25%) had rhinorrhea, 11(17.2%) had diarrhoea, and 3(4.7%) had rash. Chest radiograph revealed consolidation in the lungs of 19(29.7%) out of 64 patients. Conclusion: The spectrum of clinical features of COVID-19 among children varies from a mild to severe disease requiring critical care admission. Fever being the most common sign followed by cough, rhinorrhea and diarrhea. C-reactive protein, LDH, creatinine, total and direct bilirubin are raised during the infection in children. The children having severe disease had consolidation on chest X-ray, requiring oxygen support in critical setting.